A new short-circuit calculation method of power system with photovoltaic power sources. (July 2020) - Chen, Gang; Wu, Jiafang; Xiao, Yanhui; Hu, Jiajia; Chen, Yunchao; Zhou, Niancheng
Abstract: A large number of photovoltaic power sources connected to the grid will increase short-circuit current level of power system, and its fault transient process will change the fault characteristics of power grid. In this paper, the equivalent models of transient and steady state faults are obtained, by analysing the full current expression of photovoltaic power sources and its current characteristics in different fault stages. Based on the superposition theorem, the short-circuit current calculation method of power system with photovoltaic power sources is proposed. Finally, the effectiveness of the proposed method is verified by the analysis of actual power grid calculation examples, and the results can be used for power grid planning and relay protection setting.